Corporate Image and Internal Communication in Teachers of Licensed Universities in the Province of Huancayo, 2020 - Laredo Cárdenas, Reyna Isabel (2020)
Objective. To determine the relationship between corporate image and internal communication in teachers of licensed universities in the province of Huancayo. Methods. A descriptive study was carried out with 90 teachers from the Universidad Nacional del Centro del Peru (UNCP), Unversidad Continental (UC) and Universidad Privada Franklin Roosevelt de Huancayo (UFR) during the year 2020. In the data collection it was used as instrument the internal communication questionnaire (Nuñez, 2016) and the questionnaire on corporate image (Diaz, 2015). Spearman's rho was used for inferential analysis. Results. Findings showed that the correlation coefficient between the two variables is rho = 0.140. It represents a rare relationship; the p value is 0.189 greater than alfa = 0.05; so the null hypothesis is accepted and the alternate hypothesis is denied. Conclusion. The main finding shows in table 1 that 45.6% of the teachers surveyed express that there is a good corporate image in these higher education institutions. In addition, according to table 2, 23.3% state that there is no good internal communication within of these higher education institutions. Therefore, it is concluded that the corporate image does not depend on internal communication in licensed universities of Huancayo.